Проблеми нормативного визначення категорій «обвинувачення» та «державне обвинувачення» - Гловюк, Ірина Василівна; Гловюк, Ирина Васильевна; Glovyuk, Iryna (Одеса : Юрид. л-ра, 2012)
This article covers study of categories «incrimination» and «prosecution on behalf of a state» in the context of new Code of criminal proceedings of Ukraine. Correlation of categories «incrimination» and «criminal prosecution» has been considered, additionally it was grounded that, incrimination in the terms of legal procedure is a form of criminal prosecution.
Гловюк І. В. Проблеми нормативного визначення категорій «обвинувачення» та «державне обвинувачення» / І. В. Гловюк // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 557-563.
Keywords: обвинувачення; державне обвинувачення; підтримання державного обвинувачення; кримінальне переслідування; обвинение; государственное обвинение; поддержание государственного обвинения; уголовное преследование; incrimination; prosecution on behalf of a state; support of prosecution on behalf of a state; criminal prosecution